1981
DOI: 10.1007/bf00033666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre- and post-inoculation temperature on resistance in certain cultivars of poplar to races of Melampsora larici-populina kleb.

Abstract: Four cultivars of Populus spp., compatible to varying degrees with four races of M . larici-populina KLEB., were raised in a controlled environment on a high (28°/20°C, day/night) and low (20°/10°C) temperature regime . Leaf discs cut from the plants were inoculated separately with four individual races of M . laricipopulina and subsequently incubated at either low (20°C) or high (25°C) temperature for 14 days when disease development on the discs was assessed using three parameters (Incubation period to fleck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Discrepancies between field and laboratory results possibly result from significant differences of host physiological status and environment characteristics between both experimental conditions. Pre-and postinoculation temperatures, leaf maturity, and shoot age, for example, have been identified as key parameters influencing quantitative resistance to M. larici-populina in poplars (5,6,39). Uncontrolled variability for these parameters certainly accounts for a An asterisk indicates a situation where r 1 and R 1 genotypes exhibit significantly different correlation coefficients (non-overlapping of the 95% confidence intervals or presence of 0 in any of these two confidence intervals); ns (nonsignificant) indicates a 95% confidence interval which includes zero.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between field and laboratory results possibly result from significant differences of host physiological status and environment characteristics between both experimental conditions. Pre-and postinoculation temperatures, leaf maturity, and shoot age, for example, have been identified as key parameters influencing quantitative resistance to M. larici-populina in poplars (5,6,39). Uncontrolled variability for these parameters certainly accounts for a An asterisk indicates a situation where r 1 and R 1 genotypes exhibit significantly different correlation coefficients (non-overlapping of the 95% confidence intervals or presence of 0 in any of these two confidence intervals); ns (nonsignificant) indicates a 95% confidence interval which includes zero.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, temperature had a very small contribution to the overall weather conditions fostering rust intensity. This may initially be considered surprising given that others (Chandrashekar and Heather 1981;Widin and Schipper 1980) have reported that various components of the Melampsora pathogen life cycle (e.g., uredinia density and spore production on leaves) are dependent on temperature. However, during the period of rust development, the temperature in Altay Prefecture was 10.6 to 28.8°C over the 5-year period, which was favorable for the germination of Melampsora urediniospores and the resulting infection of leaves (Guo et al 2010;Li et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…(1980) were the first to report significant levels of isolate × clone interaction for QR to M. larici‐populina and to raise questions about potential adaptation of the pathogen. However, multi‐factorial experiments (Chandrashekar & Heather, 1981a,b; Heather & Chandrashekar, 1982a,b) showed that isolate × clone interactions accounted for negligible variations in QR when compared with isolate or cultivar main effects. Moreover, environmental factors such as light, temperature or hyperparasitism were the main contributors to QR variation, thus leading to the conclusion that in the field, the pathosystem would be well buffered against continuing selection pressure by a particular cultivar on the pathogen population.…”
Section: Introductionmentioning
confidence: 99%